Undergraduates’ interest towards learning genetics concepts through integrated stemproblem based learning approach - Abdul Rahim, Shamimah Parveen; Samsudin, Mohd Ali; Ismail, Mohd Erfy; Abdul Talib, Corrienna; Amiruddin, Mohd Hasril (2020)
Scientific and innovative society can be produced by giving priorities in Science, Technology, Engineering, and Mathematics (STEM) as emphasized by Malaysian Higher Education Blueprint (2015-2025). STEM need to be implemented at higher education because universities need to produce competent graduates to support economy growth and sustainable development. Learning STEM through Problem Based Learning might allow the undergraduates to become more enthusiastic when problem-based instruction is incorporated with STEM by implementing teamwork and problem-solving techniques to engage the first-year undergraduates fully with the learning. This study was conducted to investigate whether Integrated STEM Problem Based Learning module could enhance and retain the interest towards genetics concepts among first-year undergraduates. Topics in genetics was considered difficult not only to teach but also to learn. In this research, to overcome the genetic concepts learning difficulties, genetic related topics were chosen to introduce STEM through problem-based learning approach, which might help first-year undergraduates to acquire deep genetic content knowledge. This is very vital for the first-year undergraduates, as the knowledge gained in their first semester will be applied in the upcoming courses in their entire undergraduates’ programs of study. A Pre-Experimental research design with one group-posttest design was applied. A total of 50 participants who are first-year undergraduates from Faculty of Biology from one of the public universities in Malaysia were involved. The Genetics Interest Questionnaire used to study if the STEM Problem Based Learning module could enhance and retain the interest towards genetics concepts. The research has proven that Integrated STEM through problem-based learning approach could enhance and retains the interest in learning genetics concepts among first-year undergraduates.